Cryo-EM Grid Preparation of Membrane Protein Samples for Single Particle Analysis - Sgro, Germán G.; Costa, Tiago R. D. (Frontiers in Molecular Biosciences, 2018)
Recent advances in cryo-electron microscopy (cryo-EM) have made it possible to solve structures of biological macromolecules at near atomic resolution. Development of more stable microscopes, improved direct electron detectors and faster software for image processing, has enabled structural solution of not only large macromolecular (megadalton range) complexes but also small (~60 kDa) individual proteins. As a result of the widespread use of the technique, we have also witnessed new developments of techniques for cryo-EM grid preparation of membrane protein samples. This includes new types of solubilization strategies that better stabilize these protein complexes and the development of new grid supports with proven efficacy in reducing the motion of the molecules during electron beam exposure. Here, we discuss the practicalities and recent challenges in membrane protein sample preparation and vitrification, grid support and foil treatment in the context of the structure determination of protein complexes by single particle cryo-EM.